Post‐surgical pyoderma gangrenosum in otherwise healthy patient with history of COVID‐19. Issue 8 (24th May 2021) - Rich, Matthew D.; Sorenson, Thomas J.; Schubert, Warren
Abstract: There are increasing reports of autoimmune and dermatologic sequelae of COVID‐19. We describe an otherwise healthy patient with recent history of serious COVID‐19 infection who developed post‐surgical pyoderma gangrenosum following bilateral reduction mammoplasty and was successfully treated with infliximab, mycophenolic acid, and corticosteroids. We present this case to highlight the lingering systemic proinflammatory effects of COVID‐19 infection that may increase the risk of rare autoimmune complications of surgery. As a complete understanding of the long‐term effects of COVID‐19 is poorly understood, patients with a history of COVID‐19 infection should be appropriately counseled to these possible risks when discussing surgery.